CLINICAL AND DIAGNOSTIC EVALUATION OF THE INAPPROPRIATENESS OF CHEST RADIOGRAPHY WITHIN THE FIRST 24 HOURS IN CHILDREN WITH SUSPECTED PNEUMONIA - N. Shapambayev; T. Muratalieva; D. Nurbekova; B. Seitkhanova; Zh. Bagdaulet; G. Kakar; A. Zharylhan; N. Serik (Yassawi Journal of Health Sciences, 2026)
Pneumonia in children remains one of the most significant problems in modern pediatrics due to its high prevalence and the risk of complications associated with delayed diagnosis. Chest radiography is widely used as a standard imaging method for confirming the diagnosis; however, its use in the early stage of the disease may have limited diagnostic value and contribute to unnecessary radiation exposure. Classically, four stages of lobar pneumonia are distinguished: congestion, red hepatization, gray hepatization, and resolution. In the early stage (congestion stage), morphological changes in lung tissue are minimal, which limits the diagnostic performance of radiographic imaging. To evaluate the diagnostic appropriateness of chest radiography performed within the first 24 hours in children with suspected pneumonia and to assess the benefits of delayed imaging in reducing radiation exposure.[1] The study was conducted at City Polyclinic No. 3 in Shymkent. Radiological data from five children aged 1–3 years with clinically confirmed pneumonia were analyzed. Chest radiography was performed on the first day of illness and repeated on the third day. Additionally, a questionnaire survey of 10 general practitioners was conducted to assess clinical decision-making and awareness of radiation exposure.[2] On the first day of illness, no radiological abnormalities were detected in 100% of patients despite clinical signs of pneumonia. On the third day, all children (100%) demonstrated radiological features consistent with inflammatory changes in the lungs. Repeated imaging resulted in a twofold increase in cumulative radiation exposure. According to the survey, 70% of physicians prescribe chest radiography within the first day of illness, while only 40% are aware of its limited diagnostic value in early disease stages. Thus, chest radiography performed within the first 24 hours in children with suspected pneumonia has low diagnostic yield due to minimal morphological changes at the early stage of the disease. Delayed imaging improves diagnostic accuracy and reduces radiation exposure without compromising diagnostic quality.[3]